Cold Physical Plasmas in the Field of Hygiene—Relevance, Significance, and Future Applications. Issue 12 (December 2015) - Kramer, Axel; Bekeschus, Sander; Matthes, Rutger; Bender, Claudia; Stope, Matthias B.; Napp, Matthias; Lademann, Olaf; Lademann, Jürgen; Weltmann, Klaus‐Dieter; Schauer, Frieder
Abstract : Cold physical plasmas ignited a technological spark in industry, biotechnology, and medicine. Especially the field of hygiene benefited of the plasma's exceptional activity against pathogenic microorganisms. Together with plasma‐based surface functionalization, these qualities are highly relevant in a variety of processes in health care, such as the decontamination or sterilization of medical devices, food, packaging materials, waste water, or indoor air. In medicine, plasma has proven to show promising antiseptic results on skin and mucosal membranes in infection‐related diseases in dermatology and dentistry. This comprehensive review will discuss the current applications of cold plasma in the fields of hygiene, and will provide a promising outlook on many applications yet to come. Abstract : Owing to its exceptional microbicidal activity and compatibility, cold plasma technology possesses a tremendous potential in hygiene. We reviewed recent progress of plasma applications, including reprocessing of medical devices, decontamination in food industry, air cleaning, waste management, surface customization, wound treatment, and skin antisepsis. Exciting past, current, and future research will be helpful in solving a range of nowadays' issues.